Politeness Strategy Found in the Third Debate of Presindential Candidates for the 2024 Election - Fauziah, Meli; Widianto, Eko; Vrika, Renggi; Cardoso, Luis Miguel; Durgaryan, Alesa (ENGLISH FRANCA : Academic Journal of English Language and Education, 2024)
This study aims to investigate politeness in presidential candidate debates from the Interactional Sociolinguistics (IS) perspective. The approach was taken because there was a lack of studies that connected politeness with IS, considering that IS is great for examining social phenomena, especially sensitive conversations between high-status people. To acquire a clear insight into the phenomenon, this study uses discourse analysis on video transcripts of “The Third Debate of Presidential Candidates for the 2024 Election,” taken from the KPU RI YouTube channel. The analysis process drew on existing research to support the interpretation. The researcher analyses 170 data (clustered into 117 data of positive face and 53 data of negative face), including the frequencies and categories from the face-saving acts (FSA) and face-threatening acts (FTA). The identified aspects of Face-threatening Acts (FTAs) are criticism, threat, interruption, critical disagreement, dismission or ignorance, and demanding a satisfying response. Face-saving Acts (FSAs) identified aspects are providing equal opportunity, clarifying and apologizing, requesting cooperation, agreement while giving criticism, and providing equal opportunity. Fascinatingly, this study found that face-threatening acts sometimes necessary to use and impolite acts are acceptable if the speaker had “roles” in the conversation. Additionally, this study discovered that it is possible to measure the significance level of politeness, which will be extremely helpful for future research.